Realization of right of appeal to administrative court as guarantee of justice accessibility in administrative courts: problem questions and ways of solving of their (Journal of actual problems of jurisprudence, 2019)
The problems of law regulation and enforcement activity connected with realization of right of appeal to administrative court areanalyzed in the article. Defi nitions of legal act and individual act are grounded.